Knowledge on malaria among caregivers with children aged under 5 years at Kenyasi Health Center - Cecilia Ackon Ansong; Frank Bediako Agyei; Ramatu Agambire; Jonathan Bayuo (Journal of Integrative Nursing, 2021)
Background: Malaria remains one of the leading causes of morbidity and mortality among children under 5 years old in many low- and middle-income countries. According to the Ghana National Malaria Control Program, malaria kills at least three children every day and also tops the outpatient department cases in Ghana. Objective: The present study sought to determine the knowledge of malaria among caregivers of children under 5 years at Kenyasi Health Center, Ghana. Materials and Methods: The study was a descriptive, cross-sectional study. One hundred and three caregivers with children under 5 years old were recruited using the systematic random sampling technique, and data were collected using a structured questionnaire. Results: The findings revealed that majority (98%) of the respondents knew at least one cause of malaria. Furthermore, all respondents knew at least one complication of malaria and majority (97%) knew at least one preventive measure of malaria. Conclusion: Caregivers of children have adequate knowledge about malaria and its mode of transmission. Further education on the implementation of the preventive methods is still needed to help reduce the incidence of malaria among children.